2002
DOI: 10.1081/css-120004825
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil phosphorus sorption saturation from Mehlich-3 data

Abstract: Soil phosphorus sorption saturation (P sat ) measures the degree to which soil phosphorus (P) sorption sites have been filled and has been found to be a good indicator of P availability to runoff and leachate. At present, analytical methods required to estimate P sat are generally not offered by soil testing laboratories. This study evaluated the use of Mehlich-3 data in estimating P sat in a wide range of soils. In acidic soils ðpH ¼ 4:1-5:9Þ; P sat estimated from Mehlich-3 P, iron (Fe), and aluminum (Al) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 27 publications
1
101
1
Order By: Relevance
“…Surprisingly, the slopes of the regression lines between PSI and Mehlich 3 Al were not statistically different in the five different solution treatments (P , 0.05). It is not uncommon for metal oxides to play a strong role in P sorption in noncalcareous soils (Berkheiser et al 1980;Hsu 1964; Van der Zee and Van Riemsdijk 1986), though unlike our study most of these correlations have been observed with oxalate-extractable Al instead of Mehlich 3-extractable Al (Beauchemin et al 2003;Borggaard et al 1990;Borling, Otabbong, and Barberis 2001;Burkitt et al 2006;Kleinman and Sharpley 2002;Pierzynski et al 1990;Traina et al 1986). …”
Section: Phosphorus Sorption From Manurecontrasting
confidence: 71%
See 2 more Smart Citations
“…Surprisingly, the slopes of the regression lines between PSI and Mehlich 3 Al were not statistically different in the five different solution treatments (P , 0.05). It is not uncommon for metal oxides to play a strong role in P sorption in noncalcareous soils (Berkheiser et al 1980;Hsu 1964; Van der Zee and Van Riemsdijk 1986), though unlike our study most of these correlations have been observed with oxalate-extractable Al instead of Mehlich 3-extractable Al (Beauchemin et al 2003;Borggaard et al 1990;Borling, Otabbong, and Barberis 2001;Burkitt et al 2006;Kleinman and Sharpley 2002;Pierzynski et al 1990;Traina et al 1986). …”
Section: Phosphorus Sorption From Manurecontrasting
confidence: 71%
“…Because soil has a finite capacity to sorb P, there is much interest in obtaining accurate estimates of a soil's ability to bind additional P. An approach gaining popularity for estimating a soil's capacity to retain P is the calculation of a saturation index, sometimes referred to as the degree of P saturation (DPS) (Hooda et al 2000;Kleinman and Sharpley 2002). The DPS is a ratio of extractable P to P sorption capacity and thus quantifies the remaining sorption capability of the soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, soils with the highest PSC have the highest sum of Fe ox and Al ox contents (Figure 7). Comparable correlations of PSC with Fe ox and Al ox have been reported in the literature [24,27,33,46,54,87,[89][90][91][92]. Numerous studies [22,29,46,89,93] have shown that the most important parameters that determine the P sorption are Fe ox and Al ox .…”
Section: Soil P Sorption Kineticsmentioning
confidence: 86%
“…Higher values are associated with better crop growth but potentially more leaching potential for P. The DPS ratio was determined as well as the alternate ratio [30][31][32], P/Ca, since it is better for soils with pH > 7.…”
Section: Analyses For the Studymentioning
confidence: 99%